Spectral Matching of Three-Component Seismic Ground Accelerations for Critical Structures - Sindur P. Mangkoesoebroto; Adi Yasa; Ediansjah Zulkifli (Institut Teknologi Bandung, 2023)
Abstract This study introduces a new procedure for three-component spectral matching of seismic ground acceleration records. The procedure involves preserving the phase angle and varying the Fourier amplitudes to match the spectra of the recorded records with a provided target spectrum that represents the spectral values of ground motions in three orthogonal directions. Several three-component recorded records were matched against two target response spectra to test the method. An accurate convergence was achieved in the velocity and displacement records. In addition, the scales among the components’ magnitude were maintained, creating realistic three-component ground motions. Such ground motion inputs are important to qualify critical structures sensitive to three-component motions. Our proposed procedure is novel because the present practices are mostly created based on one-component ground motions. Keywords: Spectral matching, three components, component scales, phase angle, critical structures. Abstrak Studi ini mengusulkan prosedur baru terkait penyesuaian spektra catatan percepatan gempa. Prosedur ini dilakukan dengan mempertahankan sudut phasa tetapi mengubah amplitudo Fourier catatan percepatan gempa demikian hingga spektrumnya sesuai dengan target. Target spektrum yang diinputkan mewakili tiga komponen gempa. Untuk mengujinya, beberapa catatan gempa tiga-komponen disesuaikan spektrumnya terhadap dua target spektra. Ketelitian yang cukup baik terlihat dari catatan kecepatan dan simpangan. Skala ketiga komponen juga dijaga sehingga dihasilkan percepatan gempa tiga-komponen yang realistis. Percepatan gempa sejenis ini diperlukan dalam proses kualifikasi struktur penting yang sensitif terhadap pengaruh gerakan tiga arah. Prosedur tersebut adalah baru karena teknik yang ada sekarang didasarkan pada penyesuain spektrum per-komponen. Kata-kata Kunci: Penyesuaian spektra, tiga komponen, skala komponen, sudut phasa, struktur penting.